2021
DOI: 10.1097/bpb.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Multi-day delay to care identified in pediatric trauma cases during COVID-19

Abstract: This study aims to establish how pediatric fracture patterns were altered at a level 1 trauma center in a state that implemented a shutdown during the initial height of COVID-19. After IRB approval, we identified 2017 patients treated at a pediatric institution for definitive management of a fracture between 26 March and 31 May 2018, 2019, or 2020. Dates were chosen based on statewide stay-at-home orders for Colorado. Patients were excluded for treatment at another institution ( n = 148)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 34 publications
5
17
2
Order By: Relevance
“…8,[29][30][31][32] However, it is troubling that some centers noted concerning findings such as higher acuity, increased hospital and intensive care admission rates, and potentially delayed presentations for common serious illnesses such as appendicitis and fractures. 8,32,33 The effect of COVID-19 on the field of pediatric surgery has been profound -requiring many changes to maximize safety while maintaining the ability to do high-acuity procedures. 34 The reported effects of the pandemic on pediatric trauma have been variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,[29][30][31][32] However, it is troubling that some centers noted concerning findings such as higher acuity, increased hospital and intensive care admission rates, and potentially delayed presentations for common serious illnesses such as appendicitis and fractures. 8,32,33 The effect of COVID-19 on the field of pediatric surgery has been profound -requiring many changes to maximize safety while maintaining the ability to do high-acuity procedures. 34 The reported effects of the pandemic on pediatric trauma have been variable.…”
Section: Discussionmentioning
confidence: 99%
“…In Texas, Sanford et al 36 found overall decreased pediatric trauma, but with increased burns and penetrating injuries. A study by Shaw et al 33 from Colorado, describes an overall decrease in pediatric fractures but with increased fractures in younger children, more severe fractures in older children, and a significant increase in delayed presentation for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from 1993 through 2020 was downloaded from the ICPSR website; however, due to changes in injury patterns associated with the COVID pandemic, those data from the year 2020 were excluded [ 27 , 28 , 29 , 30 , 31 , 32 ], including firearm injuries [ 33 , 34 , 35 ]. The data includes age, sex, race, type of firearm, the perpetrator of the injury (e.g., self, stranger, etc.…”
Section: Methodsmentioning
confidence: 99%
“…We would like to share ideas on ‘Multi-day delay to care identified in pediatric trauma cases during COVID-19’ [1]. Shaw et al ., [1] found an increasing nonaccidental trauma in 2020 compared to the previous year. In fact, the impact of COVID-19 is widely reported.…”
mentioning
confidence: 99%